Phubbing and Loneliness in Single Adult: The Moderation Role of Self Esteem - Jelang Hardika; Aditya Putra Kurniawan; Martaria Rizky Rinaldi (Jurnal Online Psikogenesis, 2025)
Emerging adulthood is a life stage marked by intense social exploration and identity development. However, single individuals in this phase may face psychosocial challenges, particularly related to loneliness. This study aimed to examine the relationship between phubbing behavior and loneliness among single emerging adults, and whether self-esteem moderates this relationship. Using convenience sampling, a total of 218 single emerging adults aged 17–29 years (M = 21.71, SD = 2.05) participated in this cross-sectional study. Participants completed the Generic Scale of Phubbing (GSP), UCLA Loneliness Scale version 3, and the Single-Item Self-Esteem Scale (SISE). Data was analyzed using moderation regression via the MedMod module in Jamovi. Results showed a significant positive relationship between phubbing and loneliness. Self-esteem did not directly predict loneliness, but its interaction with phubbing was significant, indicating a moderation effect. Simple slope analysis revealed that the association between phubbing and loneliness was stronger among individuals with higher self-esteem. These findings challenge the notion that self-esteem always serves as a psychological buffer. Instead, high self-esteem may amplify the emotional consequences of digital disengagement behaviors such as phubbing. This study expands the understanding of the psychological dynamics of digital social behaviors and their impact on mental well-being among single emerging adults.